Kesiapan Guru IPA dalam Mengimplementasikan Pembelajaran Berbasis Deep Learning pada Kurikulum Merdeka - Novi Yulia Santi; Yohanes Nong Bunga; Oktavius Yoseph Tuta Mago (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
Twenty-first-century education and the Merdeka Curriculum call for deep learning-based instruction that fosters deep conceptual understanding, making teacher readiness a key factor in its successful implementation. This study analyzes science teachers' readiness in implementing deep learning-based instruction within the Merdeka Curriculum at SMPK Renha Rosario Kewapante, viewed from knowledge, skills, resource availability, and attitude. A descriptive qualitative approach was used, involving one science teacher as the main informant, supported by the principal, the vice-principal for curriculum, and two peer teachers selected through purposive sampling. Data were collected through questionnaires, semi-structured interviews, observation, and documentation, validated through source and technique triangulation, member checking, and referential adequacy, and analyzed using data reduction, display, and conclusion drawing. Results show teacher readiness is good in knowledge, skills, and attitude, and fairly good in resource availability. The teacher understood the Merdeka Curriculum and deep learning concepts and could design lesson plans based on mindful, meaningful, and joyful learning principles, yet classroom practice remained dominated by lecturing, indicating a gap between conceptual and implementative readiness. Supporting factors included school support, collaboration through learning communities and subject teacher forums, and student participation, while inhibiting factors included limited facilities, time, and sustained professional mentoring. These findings imply the need to strengthen academic supervision, practice-oriented training, and learning facilities to bridge this gap.